Antioxidant Activity, Metal Chelating Ability and DNA Protective Effect of the Hydroethanolic Extracts of Crocus sativus Stigmas, Tepals and Leaves - Sabir Ouahhoud; Amine Khoulati; Salma Kadda; Noureddine Bencheikh; Samira Mamri; Anas Ziani; Sanae Baddaoui; Fatima-Ezzahra Eddabbeh; Iliass Lahmass; Redouane Benabbes; Mohamed Addi; Christophe Hano; et al. (MDPI AG, 2022)
The present study investigated the antioxidant activity, metal chelating ability and genoprotective effect of the hydroethanolic extracts of Crocus sativus stigmas (STG), tepals (TPL) and leaves (LV). We evaluated the antioxidant and metal (Fe2+ and Cu2+) chelating activities of the stigmas, tepals and leaves of C. sativus. Similarly, we examined the genotoxic and DNA protective effect of these parts on rat leukocytes by comet assay. The results showed that TPL contains the best polyphenol content (64.66 µg GA eq/mg extract). The highest radical scavenging activity is shown by the TPL (DPPH radical scavenging activity: IC50 = 80.73 µg/mL). The same extracts gave a better ferric reducing power at a dose of 50 µg/mL, and better protective activity against β-carotene degradation (39.31% of oxidized β-carotene at a 100 µg/mL dose). In addition, they showed a good chelating ability of Fe2+ (48.7% at a 500 µg/mL dose) and Cu2+ (85.02% at a dose of 500 µg/mL). Thus, the antioxidant activity and metal chelating ability in the C. sativus plant is important, and it varies according to the part and dose used. In addition, pretreatment with STG, TPL and LV significantly (p < 0.001) protected rat leukocytes against the elevation of percent DNA in the tail, tail length and tail moment in streptozotocin- and alloxan-induced DNA damage. These results suggest that C. sativus by-products contain natural antioxidant, metal chelating and DNA protective compounds, which are capable of reducing the risk of cancer and other diseases associated with daily exposure to genotoxic xenobiotics.